The associations of radiological features of high-resolution computed tomography with the outcomes of transbronchial cryobiopsy in interstitial lung diseases: A cohort study - Zhou, Guowu; Ren, Yanhong; Li, Jun; Yang, Ting; Su, Nan; Zhao, Ling; Wang, Shumeng; Wang, Dan; Li, Ying; Tian, Zheng; Liu, Ruihong; Dai, Huaping; et al. (Frontiers in Medicine, 2022)
Background: Transbronchial cryobiopsy (TBCB) is critical procedure in the diagnosis interstitial lung diseases (ILD). The associations between high-resolution computed tomography (HRCT) features and outcomes of TBCB were unknown. Methods: This study was analyzed from a single-center prospective cohort study between September 2018 and January 2020 (NCT04047667). HRCT was obtained before TBCB. The clinical and radiological characteristics, complications, pathological and multidisciplinary discussion (MDD) diagnoses were recorded. The relationships between HRCT features and outcomes of TBCB were analyzed. Results: TBCB was performed on 216 ILD patients. The radiological probable usually interstitial pneumonia (UIP), indeterminate for UIP, ground-glass opacities (GGO) and cysts were found in 55 (25.5%), 38 (17.6%), 84 (38.9%) and 9 (4.2%) patients, respectively. And 118 (54.6%) patients had high HRCT score (involved lung proportion ≥50%) in the biopsied lobe. Multivariate analysis suggested radiological probable UIP pattern may be an independent risk factor for moderate bleeding (OR=4.304; 95%CI: 1.383-13.393; P=0.012), while GGO may be a protective factor from moderate bleeding (OR=0.173, 95%CI: 0.043-0.687; P=0.013). The pathological diagnostic yield in patients presenting cysts on HRCT was significantly lower than others (44.4% versus 87.9%; P=0.009). While performing TBCB in the lobe with high HRCT score increased pathological diagnostic yield (91.5% versus 79.6%; P=0.022). The HRCT features were not associated with pneumothorax, nor the MDD diagnostic yields. Conclusions: HRCT features were associated with moderate bleeding and pathological diagnosis. Pre-TBCB assessments of HRCT pattern and scores were helpful for bronchoscopists to make a better patient selection and procedure planning